International Journal of Intelligent Transportation Systems Research - Prathombutr, Passakon; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal is the only transportation journal to report on multi-disciplinary research efforts with the goal to discover solutions to difficult issues in the field. It provides a platform to bring together researchers and specialists in the fields of transportation, electrical, mechanical and traffic engineering, as well as those in the areas of policy planning, economics, and psychology, for wide-ranging discussion about future transportation systems. The journal is the global forum for transportation research. Papers published include original research in such areas as: Sensor Technology Imaging, Laser, Induction Coil, Ultrasonic Sensor and Recognition Technology based on the above mentioned technologies. Communication Technology and its Applications Infrared Beacon, Radio Wave DSRC (Dedicated Short Range Communication), ETC (Electronic Toll Collection System), Navigation System Vehicle Control and Automated Driving AHS (Advanced Cruise-Assist Highway System), ACC (Adaptive Cruise Control), Lane-Keep, Automatic Driving, Automatically Operated Bus Safety Improvement and Human Interface ASV (Advanced Safety Vehicle), Cruise Assist, Simulator Traffic Control Incident Detection System, Traffic Measurement, Signal Control, Accident Management Traffic Planning Road Planning, Signal Planning, Traffic Simulation Urban Engineering Urban Space Modelling, Urban Planning Transportation Policy, Traffic Economy Creation & Improvement of Pertinent Laws and Regulations, TDM (Transportation Demand Management), Road Pricing, Privacy Protection Traffic Psychology Drivers, Pedestrians and Vulnerable Road Users Other Applied Technologies.
Keywords: User interfaces (Computer systems).; Computer graphics; Automotive engineering; Robotics; Automation; Civil engineering; Electrical engineering; Electrical Engineering; Automotive Engineering; Robotics and Automation; Computer Imaging, Vision, Pattern Recognition and Graphics; Civil Engineering; User Interfaces and Human Computer Interaction